2004
DOI: 10.1086/424665
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Weight and Lean Body Mass during Highly Active Antiretroviral Therapy

Abstract: HAART had modestly favorable effects on body composition, particularly in patients with greater pretreatment immunocompromise and virological compromise. The difference between antiretroviral-naive and antiretroviral-experienced subjects with regard to the ability to achieve increased body weight and LBM requires more study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 27 publications
3
46
0
1
Order By: Relevance
“…The mean BMI was marginally higher among adherent compared with non-adherent respondents, but there was no statistical significance. These increases in weight and BMI in this study are consistent with those reported in the literature (Shikuma et al, 2004;Esposito et al, 2008;Quaye and AddaiMensah).Studies have reported relationship between HAART induced decrease in virus burden, increased CD4 cell count and increased mean weight and BMI (Shikuma et al, 2004;Esposito et al, 2008). In this study, it was found that there was a mean increase in CD4 cell count and mean weight and BMI increases from initiation of HAART, indicating increase in weight is related to viral suppression and immunological response.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean BMI was marginally higher among adherent compared with non-adherent respondents, but there was no statistical significance. These increases in weight and BMI in this study are consistent with those reported in the literature (Shikuma et al, 2004;Esposito et al, 2008;Quaye and AddaiMensah).Studies have reported relationship between HAART induced decrease in virus burden, increased CD4 cell count and increased mean weight and BMI (Shikuma et al, 2004;Esposito et al, 2008). In this study, it was found that there was a mean increase in CD4 cell count and mean weight and BMI increases from initiation of HAART, indicating increase in weight is related to viral suppression and immunological response.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies in both developed and developing countries have reported that optimal adherence (≥ 95%) correlated with a viral load decrease, CD4 cell count increase, total lymphocyte counts, haemoglobin concentrations and higher survival rates (Gross et al, 2006;Ferradini, 2006;Nieuwkerk and Oort, 2006;Gutierrez, 2006;Tang et al, 2011;Shikuma et al, 2004;Esposito et al, 2008;Quaye and Addai-Mensah, 2011).Non-adherence has also been associated with increased viral load, emerging drug resistance, increased morbidity and mortality (Brinkhof et al, 2009;Gazzola et al, 2009;Bangsberg et al, 2007).There have been mixed results of adherence rates in Africa and specifically in Nigeria with most studies reporting optimal adherence rates (Peltzer, 2010;Chabikuli 2010;Ohene and Forson, 2009;Monjok et al, 2010;Akileswaran, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to the present knowledge, there are no data indicating that adiposity or growth disorders influence the immunologic defense against viral infections. Infections such as the acquired immunodeficiency syndrome (AIDS) [46] or rare congenital viral infections [22,23], which may be associated with lipometabolic disturbances or growth disorders, were precluded from this study on the basis of patients' laboratory data and history.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to HAART has been associated with relative improvements in immunologic and virologic markers (Low-Beer et al, 2000;Paterson et al, 2001), increased body weight (Shikuma et al, 2004), and less rapid progression to Acquired Immunodeficiency Syndrome (AIDS; Bangsberg et al, 2001). Despite the seriousness of problems related to nonadherence, empirical studies on HAART adherence interventions for HIV-positive substance users are lacking (Simoni et al, 2005).…”
Section: Introductionmentioning
confidence: 99%